Donepezil as a new therapeutic potential in KCNQ2- and KCNQ3-related autism - Nissenkorn, Andreea; Bar, Lior; Ben-Bassat, Ariel; Rothstein, Lynn; Abdelrahim, Hoda; Sokol, Riki; Gabis, Lidia V.; Attali, Bernard (Frontiers in Cellular Neuroscience, 2024)
Introduction: The KCNQ2/KCNQ3 genes encode the voltage-gated K channel underlying the neuronal M-current, regulating neuronal excitability. Loss-of-function variants cause neonatal epilepsy, treatable with the M-current-opener retigabine, which is no longer marketed due to side effects. Gain-of-function variants cause developmental encephalopathy and autism that could be amenable to M-current, but such therapies are not clinically available. In this translational project, we investigated whether donepezil, a cholinergic drug used in Alzheimer, suppresses M-currents in vitro and improves cognitive symptoms in patients with gain-of-function variants. Method: 1- The effect of 1 µM donepezil on the amplitude of the M-current was measured in excitatory and inhibitory neurons of mouse primary cultured hippocampal cells. M-current was measured using the standard deactivation protocol (holding at 0 mV and deactivation at −60 mV) in the voltage-clamp configuration of the whole-cell patch-clamp technique. The impact of donepezil was also examined on the spontaneous firing activity of hippocampal neurons in the current-clamp configuration. 2-Four children with autism, aged 2.5- 8 years with the following gain-of-function variants were enrolled: KCNQ2(p. Arg144Gln) and KCNQ3(p.Arg227Gln, p.Arg230Cys). Patients were treated off-label with donepezil 2.5-5mg/d for 12 months and assessed with: Clinical-Global-Impression-of-Change (CGI-c), Childhood-Autism-Rating-Scale-2 (CARS-2), Adaptive-Behavior-Assessment-System-II (ABAS-II) and Child-Development-Inventory (CDI). Results: 1-Application of donepezil for at least 6 min produced a significant inhibition of the M-current with an IC50 of 0.4 µM. At 1 µM, donepezil reduced by 67% the M-current density of excitatory neurons (2.4±0.46 vs.0.89±0.15 pA/pF, p<0.05*). In inhibitory neurons, application of 1 µM donepezil produced a lesser inhibition of 59% of the M-current density (1.39±0.43 vs. 0.57±0.21, p>0.05). Donepezil (1 µM) potently increased by 2.6-fold the spontaneous firing frequency, which was prevented by the muscarinic receptor antagonist atropine (10 µM). 2-The CARS2 decreased by 3.8±4.9 points(p>0.05), but in two patients with KCNQ3 variants, the improvement was over the 4.5 clinically relevant threshold. Global clinical change was also clinically significant in these patients (CGI-c=1). The CDI increased by 65% (p<0.05*) , while the ABAS-II remained unchanged. Discussion: Donepezil should be repurposed as a novel alternative treatment for gain-of-function variants in KCNQ2/KCNQ3 encephalopathy.